High Prevalence of Post-stroke Anxiety in Elderly Patients Following COVID-19 Outbreak - Yao, Meiling; Li, Hongjie; Luo, Ying; Li, Ling; Yu, Jian (Frontiers in Psychiatry, 2021)
Objective: Post-stroke anxiety (PSA) is a common affective disorder in patients with ischemic stroke. The elderly are more susceptible to mental health issues, however, few studies have so far focused on PSA in elderly patients, especially in the context of the COVID-19, causing psychological issues in the general population. The aim of the present study was to assess the prevalence and risk factors of PSA in elderly patients following COVID-19 outbreak. Methods: We retrospectively analyzed 206 elderly inpatients with newly diagnosed acute ischemic stroke in the First Affiliated Hospital, Sun Yat-sen University, from January 2020 to December 2020. Patients were categorized into the PSA group and the non-PSA group based on Hamilton Anxiety Scale scores at admission (within 1 week after stroke onset). Demographic and clinical data, mental state by Mini-Mental State Examination, depression by Hamilton Depression Scales (HAMD), and stroke severity and outcome by National Institutes of Health Stroke Scale (NIHSS) and modified Rankin Scale were compared between the two groups. Univariate analysis and binary logistic regression analysis were used to analyze risk factors associated with PSA. We determined the cutoff scores for significant predictors of PSA using the area under the curve (AUC) and receiver operating characteristic. Results: Of the 206 stroke patients, 62 (30.1%) developed anxiety. Binary logistic regression analysis showed that female gender [adjusted odds ratio (aOR): 2.288, 95% confidence interval (CI):1.021–5.128, P = 0.044], high NIHSS scores [aOR: 1.264, 95% CI: 1.074–1.486, P = 0.005] and HAMD scores [aOR: 1.345, 95% CI: 1.215–1.490, P < 0.001] were independent risk factors for PSA. The cutoff threshold for the NIHSS scores was 3.5 points with an AUC of 0.64 and the cutoff threshold for HAMD scores was 5.5 points with an AUC of 0.89. Conclusion: Our results showed a high incidence of PSA in elderly patients after the COVID-19 outbreak. Female gender, high NIHSS and HAMD scores were the independent risk factors for PSA.